CIVIL-MILITARY RELATIONS IN DISASTER RESCUE AND RELIEF ACTIVITIES: RESPONSE TO THE MUDSLIDE IN SOUTHERN LEYTE, PHILIPPINES - Hall, Rosalie Arcala; Cular, Anita (Scientia Militaria - South African Journal of Military Studies, 2011)
This article examines engagements between civilian actors, the Philippine security forces and the US military during disaster response operations. The Philippine disaster framework recognises the military’s role in disaster relief and has existing mechanisms for accepting international assistance and procedures for military-to-military cooperation in this task. The local authorities accord the military a central role in the disaster operations, contrary to notions of it being the ‘last resort’. Tasking and coordination proceeded separately along civilian versus military lines, with limited interface between the two groups. The army reservists had greater linkages with civilian actors than did the army regulars, who dealt exclusively with the foreign teams. The US military’s activities were confined to search and rescue and to providing critical logistics, which the Philippines actors lacked.